A Study On The Dual Application Of Black Soldier Fly Larvae (Hermetia Illucens): Protein-Rich Animal Feed And Biological Polyhydroxybutyrate (Phb) Extraction Agent - Mohamad, Lydia (2021)
This study investigated the effect of different feeding strategies of black soldier fly larvae (BSFL) on the crude protein content of black soldier fly pre-pupae (BSFP) and to biologically extract the polymer by modifying the diet with bacterial cells containing polymer, PHB.